Core–shell silica–rhodamine B nanosphere for synthetic opals: from fluorescence spectral redistribution to sensing. Issue 25 (16th April 2020) - Lova, Paola; Congiu, Simone; Sparnacci, Katia; Angelini, Angelo; Boarino, Luca; Laus, Michele; Di Stasio, Francesco; Comoretto, Davide
Abstract : Silica nanospheres were functionalized with rhodamine B and self-assembled into opals. Photoluminescence redistribution and pollutant responsivity were also investigated. Abstract : Photonic crystals are a unique tool to modify the photoluminescence of light-emitting materials. A variety of optical effects have been demonstrated by infiltrating opaline structures with photoactive media. On the other hand, the fabrication of such structures includes complex infiltration steps, that often affect the opal lattice and decrease the efficiency of light emission control. In this work, silica nanospheres were directly functionalized with rhodamine B to create an emitting shell around the dielectric core. Simple tuning of the microsphere preparation conditions allows selecting the appropriate sphere diameter and polydispersity index approaching 5%. These characteristics allow facile self-assembling of the nanospheres into three-dimensional photonic crystals whose peculiar density of photonic states at the band-gap edges induces spectral redistribution of the rhodamine B photoluminescence. The possibility to employ the new stable structure as sensor is also investigated. As a proof of principle, we report the variation of light emission obtained by exposure of the opal to vapor of chlorobenzene.